Analisis Pengendalian Persediaan Bahan Baku Dengan Metode EOQ Pada Produk Obat Anti Nyamuk Bakar Manguni - Siwi, Max O (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: Â The purpose of this study was to determine the inventory control of raw materials by using EOQ method to prevent freezing and waste of funds. The method used in this research is descriptive quantitative conducted by collecting, summarizing and interpreting data. Further processed and analyzed again to obtain the expected results. The results showed that when using the EOQ method will get the raw material procurement cost savings. Thus, there is a difference between wisdom inventory conducted by the company with the calculation according to the EOQ. By using EOQ, cost the company less than the inventory policies of the company. EOQ method is considered to be one of the appropriate methods in the procurement of raw materials companies. Key words: Control, Raw Materials, Economic Order Quantity (EOQ)